The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s13063-019-3828-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing violent discipline by teachers using Interaction Competencies with Children for Teachers (ICC-T): study protocol for a matched cluster randomized controlled trial in Tanzanian public primary schools

Abstract: BackgroundDespite the existing national and international plans of action to end violent discipline strategies used by teachers in schools, they still prevail in Tanzanian schools. This underlines the need to implement school-based interventions that aim at reducing violent discipline by teachers. In this study, we will evaluate the feasibility and effectiveness of the preventative intervention Interaction Competencies with Children – for Teachers (ICC-T) in Tanzanian primary schools. Following its success in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…Al respecto, cabe señalar que los castigos que la docente aplica como por ejemplo, evitar que los alumnos desobedientes salgan al patio a la hora de recreo, son inadecuados, pues, según Soto (2017), el castigo debe ser la última opción, luego de intentar aplicar otro tipo de procedimientos correctivos. Tal situación es preocupante, pues como indican Bwire et al (2020), este estilo de disciplina perjudica el desarrollo académico y socioafectivo de los menores. Por el contrario, se ha comprobado que un estilo de disciplina consciente o positivo genera muchos más beneficios, además de incrementar los niveles de motivación (Aragão et al, 2017;Chávez et al, 2017;Jiménez, 2018;Silupu, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…Al respecto, cabe señalar que los castigos que la docente aplica como por ejemplo, evitar que los alumnos desobedientes salgan al patio a la hora de recreo, son inadecuados, pues, según Soto (2017), el castigo debe ser la última opción, luego de intentar aplicar otro tipo de procedimientos correctivos. Tal situación es preocupante, pues como indican Bwire et al (2020), este estilo de disciplina perjudica el desarrollo académico y socioafectivo de los menores. Por el contrario, se ha comprobado que un estilo de disciplina consciente o positivo genera muchos más beneficios, además de incrementar los niveles de motivación (Aragão et al, 2017;Chávez et al, 2017;Jiménez, 2018;Silupu, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…Global and continental initiatives such as goal 16:2 of the United Nations’ Sustainable Development Goals 2030 [ 40 ] and the African Charter on the Rights and Welfare of the Child [ 41 ] may pave the way for legal and political changes. However, there is also a high need for preventive interventions at the school-level to reduce the use of violence by teachers and school staff against children and adolescents, particularly in sub-Saharan African countries where violent discipline at schools is both highly prevalent and socially accepted [ 4 , 17 , 42 ]. Notwithstanding, although non-governmental organizations have recently introduced a number of programs in low-and middle-income settings, few of them have been rigorously evaluated in terms of their efficacy to reduce violence by teachers [ 5 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on attachment, behavioral and social learning theories, ICC-T aims to reduce the use of physical and emotional violence by teachers against students and to improve teacher-student interactions by enabling teachers to learn and practice essential interaction competencies with children [ 23 , 42 ]. Cluster randomized controlled trials at primary and secondary schools in Tanzania and Uganda have provided initial evidence for the feasibility and effectiveness of ICC-T to decrease teachers’ positive attitudes towards violence as well as student- and teacher-reported use of violence against students [ 3 , 4 , 42 ]. In a trial at Tanzanian primary schools, ICC-T also led to a reduction in student-reported victimization by peers, suggesting a spill-over effect of the intervention on peer violence [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E apesar de o Brasil ser um dos países que proíbe a violência contra estudantes de qualquer nível, ainda encontramos casos onde esta persiste em acontecer. Nestes casos, a violência (e não apenas a psicológica) imposta por professores contra estudantes pode ser vista como útil, como uma boa forma de disciplinar o processo de aprendizagem, manter o poder, desenvolver boa conduta e melhorar o desempenho acadêmico através da obediência e do controle comportamental (Ba-Saddik & Hattab, 2012;Masath, Hermenau, Nkuba & Hecker, 2020). A violência disciplinar física, tida como "instrumento pedagógico" é considerada, por seus apoiadores, mais eficaz com estudantes mais jovens, sendo o abuso psicológico a que prevalece com estudantes mais velhos (Ba-Saddik & Hattab, 2012; Lee, 2015), porém, toda forma de violência fere a dignidade do(a) estudante e traz repercussões danosas à vítima nos mais diversos aspectos.…”
Section: Introductionunclassified